Examining health system responsiveness and social exclusion among migrants utilising Gauteng public health services - White, Janine Anthea (My University, 2021)
Background The context of this PhD study is the global goal of universal health coverage (UHC) and the dearth of empirical studies on migrants’ perceptions of health system responsiveness and their experiences of social exclusion in the health systems of African host countries. Aim The overall aim of the study was to examine health system responsiveness and social exclusion among migrants in the public health sector in the Gauteng Province of South Africa. The specific objectives of the study were to: 1. Explore whether legislation, health policies and the perspectives or actions of health policy actors facilitate UHC for migrants, or exacerbate their exclusion. 2. Explore the environment of health care provision to migrants. 3. Determine the experiences of migrants utilising health care services in Gauteng. 4. Determine health care providers’ perceptions of delivering health services to migrants in Gauteng. Methodology Between 2015 and 2018, a cross-sectional mixed methods study was conducted in 13 public health facilities in the Gauteng Province of South Africa. Drawing on health system responsiveness and social exclusion theories, this PhD study consisted of four components: in-depth interviews with 18 key informants combined with a document analysis; ethnographic observations at 13 public health care facilities; a survey among 251 migrant patients; and a survey among 277 health care providers. STATA® 15 was used for quantitative data analysis, while thematic analysis was used to analyse the qualitative data. Results Paradoxically, legislation and health policies in South Africa both facilitate and exclude health care for migrants. The rights-based South African Constitution and the National Health Act are enabling, whereas the Immigration Act and draft 2019 National Health Insurance Bill are exclusionary. This legislative disjuncture is exacerbated by variations in the content, interpretation and/or implementation of policies at the provincial level. The ethnographic observations revealed busy, frantic or nervous health care spaces and contestations between patients and health workers, and among health workers. The presence of migrant patients during busy periods served as a detonator for rude or discriminatory remarks, exacerbated by staff shortages and language barriers. In the migrant patient survey, 94.3% reported that the consulting nurse or doctor listened to them and 89.4% said that they received information about their condition. However, 81.7% did not know the name of the consulting nurse or doctor and 30.0% of patients complained about waiting too long. The mean patients’ satisfaction scores with health workers were 7.0 (95% CI 6.42-7.63) for clerks, 7.4 (95% CI 7.1- 7.6) for nurses and 8.3 (95% CI 7.93-8.63) for doctors. The predictors of patient satisfaction with nurses included receipt of information about their condition; polite treatment; time spent at the health facility; and receiving prescribed medicines. In the health care provider survey, 21.0% reported that they had witnessed discrimination against migrants, while 22.6% reported differential treatment of migrant patients. Exclusionary perspectives among health care providers varied by socio-demographic and employment characteristics, including health care provider category and the type of health care facility. Conclusion The PhD generated new knowledge on health system responsiveness, social exclusion and the experiences of international migrants in Gauteng public health services. The findings highlight the need for investment in a migrant-sensitive health system as part of South Africa’s quest for UHC.
A thesis completed by published work Submitted to the School of Public Health, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, November 2021